Research on Exaptriate Stress - FENG, YUE (2019)
Globalization has made the flow of capital, information, technology and human resources more widespread and convenient. If multinational enterprises want to realize their globalization and internationalization strategy, they must deploy more managers around the world to assist the operation and development of overseas subsidiaries. As a result, the demand for expatriates is increasingly growing. However, when expatriates are sent to overseas departments to manage the company's business, they have to face the stress during the period of the adjustment working aboard. Lazarus (1969) and Black (1991) have mentioned that expatriate adjustment is accompanied by expatriate stress. On the basis of the previous research, this study analyzes the important factors for the pressure of expatriates from the aspects of work, family and culture, with expatriates from two Chinese enterprises taken as survey participants. In addition, according to the data collected from the questionnaire, this study also identifies the impact of the expatriate pressure on employees and how enterprises and individuals should deal with the expatriate pressure.